Letters and diaries - Pengilly family; Burrow, James (1855)
1. Two letters (1857). 2. Photocopies of a diary (1916-1919) written during overseas service in 1st AIF, and notes taken on board the ship "Clyde" bound from England to Australia (Sept. 1876). 3. Letter written in 1855 from James Burrow a "British soldier before Sebastopol".
Manuscript reference: NLA MS 6502.
Keywords: Burrow, James; Clyde (Ship); Medic (Steamship : 1899-1927); World War, 1914-1918 -- Personal narratives, Australian; Crimean War, 1853-1856 -- Personal narratives, English; Soldiers